Preparation of adsorbing material and method for removing heavy metal cadmium in rice field soil by using adsorbing material

By using adsorbent materials prepared by hollow glass microbeads and sodium alginate, combined with ferric chloride activation technology, the secondary pollution problem during cadmium removal in rice soil was solved, and efficient and sustainable cadmium removal effect was achieved.

CN119565572APending Publication Date: 2025-03-07SOUTHWEST UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411683917.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has the risk of secondary pollution when removing cadmium from rice soil, and long-term use of soil passivating agents will damage soil structure and microbial activity, affecting the sustainable development of agriculture.

Method used

Hollow glass microbeads and sodium alginate are used as raw materials to prepare adsorption materials, and cadmium ions in rice soil are activated by ferric chloride, combined with the efficient adsorption of adsorption materials, and the complete removal of cadmium is achieved.

Benefits of technology

Effectively remove heavy metal cadmium from rice soil, avoid secondary pollution, and easy recycling of adsorbed materials, which is conducive to the sustainable development of agriculture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005148989180000011
    Figure HDA0005148989180000011
Patent Text Reader

Abstract

The invention relates to the technical field of soil remediation, and particularly discloses an adsorption material, a preparation method thereof and a method for removing heavy metal cadmium in a paddy field, and the preparation method comprises the following steps: (1) treating hollow glass beads with an alkali solution for later use; (2) adding sodium alginate into pure water, and stirring to obtain a sodium alginate solution with the mass fraction of 1-2.5%; and (3) adding the hollow glass beads treated in the step (1) into a sodium alginate solution, uniformly stirring to obtain a hollow glass bead-sodium alginate solution, then sucking the hollow glass bead-sodium alginate solution by using an injector, dropwise adding the hollow glass bead-sodium alginate solution into a 0.1-0.5 mol / L calcium chloride solution, standing for 12-24 hours, filtering, washing and freeze-drying to obtain the adsorption material. The heavy metal cadmium in the rice soil can be effectively removed, secondary pollution cannot be caused, and the adsorption material is beneficial to recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soil remediation, relates to the removal of heavy metal cadmium in paddy soil, and particularly relates to an adsorption material and a preparation method thereof, and a method for removing heavy metal cadmium in paddy soil. Background Art

[0002] Cadmium (Cd) is a highly toxic heavy metal element widely present in the natural environment. It has the characteristics of long half-life, strong environmental mobility, easy biological absorption and irreversibility. The main emission sources are divided into natural emission sources and anthropogenic emission sources. The natural source is mainly heavy metals in soil parent materials. The anthropogenic source is mainly human activities that lead to increased heavy metal content in the soil, such as traffic emissions, smelting products and other industries, mineral mining, sewage irrigation or unreasonable fertilization in agricultural areas, commercial activities, solid waste dumping, etc. Cadmium in the environment will cause pollution and damage to soil and water bodies, and cause serious harm to microorganisms, animals and plants in soil and water bodies.

[0003] At present, soil mainly uses two strategies to treat cadmium in paddy soil: one is to reduce the activity and migration of cadmium in soil; the other is to reduce the content of cadmium in soil. Among these strategies, the technology of in situ immobilization by adding passivators or deactivators to soil is widely used. It usually refers to the introduction of passivators to change the physical and chemical properties of soil or directly adsorb heavy metals, thereby reducing the bioavailability of heavy metals. However, there are also many problems. First, in order to maintain effectiveness, passivators need to be continuously and annually invested. In addition, long-term use of soil passivators will destroy the structure of soil aggregates, inhibit microbial activity, and lead to reduced yields. Third, cadmium immobilized by passivators can be desorbed in soil after environmental changes such as acidic deposition, temperature fluctuations and fertilization. Once the soil environment changes, the fixed heavy metals may be reactivated, causing secondary pollution. Therefore, from the perspective of sustainable agricultural development, how to completely remove cadmium from contaminated soil is a technical problem that technicians in this field hope to solve. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an adsorption material and a preparation method thereof and a method for removing heavy metal cadmium in paddy soil. The present invention can effectively remove heavy metal cadmium in paddy soil without causing secondary pollution, and the adsorption material is conducive to recycling and reuse.

[0005] The technical solution of the present invention is achieved in this way:

[0006] A method for preparing an adsorbent material comprises the following steps:

[0007] (1) treating the hollow glass microspheres with an alkaline solution and setting aside;

[0008] (2) adding sodium alginate into pure water and stirring to obtain a sodium alginate solution with a mass fraction of 1 to 2.5%;

[0009] (3) adding the hollow glass microspheres treated in step (1) into the sodium alginate solution and stirring evenly to obtain a hollow glass microsphere-sodium alginate solution, then aspirating the hollow glass microsphere-sodium alginate solution with a syringe and adding dropwise into a 0.1-0.5 mol / L calcium chloride solution, letting it stand for 12-24 hours, filtering, washing, and freeze-drying to obtain the adsorption material.

[0010] Furthermore, the alkaline solution is a sodium hydroxide solution.

[0011] Furthermore, the specific steps of alkali treatment of hollow glass microspheres are: adding the hollow glass microspheres to an alkali solution, then heating in a water bath at 70-90°C, stirring at a speed of 150-200 r / min for 90-120 min, standing and cooling, filtering the alkali solution, washing with anhydrous ethanol and pure water three times each, and drying.

[0012] Furthermore, the mass ratio of sodium alginate to hollow glass microspheres is 1:3-4.

[0013] The present invention also provides a method for removing heavy metal cadmium from paddy soil using the above-mentioned adsorption material, which specifically comprises the following steps:

[0014] S1. Activation: Add 0.02-0.05 mol / L ferric chloride aqueous solution to paddy soil, stir and activate for 24-36 hours, so that the fixed cadmium in the paddy soil is converted into cadmium ions;

[0015] S2. Adsorption: Add the adsorption material described above and stir for at least 72 hours;

[0016] S3. Flotation: Recover the adsorbent material floating on the water surface, desorb and wash the adsorbent material to achieve the recycling of the adsorbent material.

[0017] Furthermore, the mass ratio of paddy soil to the ferric chloride aqueous solution is 1:1.5-2.5.

[0018] Furthermore, the dosage of the adsorption material is: the mass of the adsorption material is 0.5%-1% of the mass of the paddy soil.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention uses hollow glass microspheres and sodium alginate as raw materials to prepare adsorption materials. Sodium alginate hydrogel contains a large number of hydrophilic groups such as hydroxyl and carboxyl groups, which can effectively adsorb heavy metal cadmium; hollow glass microspheres are hollow, thin-walled closed spherical structures with rarefied gas inside, and have the characteristics of low density, low thermal conductivity and high compressive strength. Borosilicate glass formed at high temperature (>1400C) has stable chemical properties. The true density of hollow glass microspheres is 0.12-0.70g / cm 3 , thermal conductivity is 0.038~0.085WQm -1 QK -1 At the same time, hollow glass microspheres generally do not react with substrates or other substances. The present invention wraps the hollow glass microspheres on the surface of sodium alginate hydrogel, which can effectively reduce the overall density of the adsorption material and make it float on the water surface, thereby efficiently adsorbing cadmium ions without causing secondary pollution and facilitating the recycling of the adsorption material by flotation.

[0021] 2. The present invention uses ferric chloride to activate heavy metal cadmium in paddy soil. Ferric chloride can provide metal ions Fe 3+ , can exchange ions with cations in the soil and replace Cd 2+ Strong ability makes Cd 2+ activated into the solution. 2+ It also reacts with the anionic groups in the activation solution to form a stable chelate, making it difficult for the soil or plants to absorb it. 3 It can also hydrolyze to produce more H + , in order to maintain a low pH reaction environment, thereby dissolving more carbonate-bound Cd 2+ , Cd 2+ It can also react with Cl in the solution - The formation of a stable chelate facilitates the subsequent removal of Cd 2+ Efficient adsorption and complete removal. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 -SEM images of hollow glass microspheres (HGMS), SA-1.5 and HGMs@SA-1.5 after alkali treatment in Example 1.

[0023] Figure 2 -Thermogravimetric analysis of HGMs@SA-1.5 in Example 1.

[0024] Figure 3 -Strain curves of SA-1.5 and HGMs@SA-1.5 in Example 1.

[0025] Figure 4- Adsorption curves of SA-1, SA-1.5, SA-2 and SA-2.5.

[0026] Figure 5 - Effect of HGMs@SA-1.5 on Cd in Example 2 2+ Isotherm adsorption curve.

[0027] Figure 6 - Effect of HGMs@SA-1.5 on Cd in Example 3 2+ The adsorption kinetic curve.

[0028] Figure 7 - Effect of HGMs@SA-1.5 on Cd at different pH in Example 4 2+ The adsorption curve. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0030] Example 1

[0031] A method for preparing an adsorbent material comprises the following steps:

[0032] (1) adding hollow glass microspheres to a 0.5 mol / L sodium hydroxide solution, wherein the mass volume ratio of the hollow glass microspheres to the sodium hydroxide solution is 1 g:30 mL, then heating in a water bath at 80° C., stirring at a speed of 200 r / min for 90 min, standing and cooling, filtering the sodium hydroxide solution by suction, washing with anhydrous ethanol and pure water three times each, and drying to obtain alkali-treated hollow glass microspheres for standby use;

[0033] (2) Six portions of sodium alginate with different mass fractions were added into pure water and stirred to obtain sodium alginate solutions with mass fractions of 0.5%, 1%, 1.5%, 2%, 2.5% and 3%, respectively; then, sodium alginate solutions with different mass fractions were drawn with a syringe and added dropwise into a 0.1 mol / L calcium chloride solution (when the mass fraction of sodium alginate was 0.5%, the obtained solution was too dilute to prepare spherical adsorption materials; when the mass fraction of sodium alginate solution was 3%, the solution viscosity was relatively large and adsorption materials could not be prepared); the other four portions were allowed to stand for 12 hours, filtered, washed repeatedly with pure water for 3 times, and freeze-dried to obtain adsorption materials (SA-1, SA-1.5, SA-2, and SA-2.5, respectively).

[0034] (3) adding the alkali-treated hollow glass microspheres of step (1) into a sodium alginate solution having a mass fraction of 1.5% and stirring evenly, wherein the mass ratio of the hollow glass microspheres to the sodium alginate is 3:1, and obtaining a hollow glass microsphere-sodium alginate solution (HGMs@SA-1.5).

[0035] 1. The hollow glass microspheres (HGMS), SA-1.5 and HGMs@SA-1.5 treated with alkali in step (1) were characterized by SEM. The SEM images obtained are as follows: Figure 1 As shown, Figure 1 The three pictures from left to right are SEM images of hollow glass microspheres (HGMS), SA-1.5 and HGMs@SA-1.5 after alkali treatment. It can be seen from the pictures that HGMs are spherical in shape and have a relatively smooth surface; the surface of SA-1.5 is very smooth without other impurities; HGMs@SA-1.5 is in the form of spherical particles of about 2 mm, and the surface is rough and porous, and HGMs are attached to the surface of SA.

[0036] At the same time, the alkali-treated hollow glass microspheres HGMS and HGMs@SA-1.5 were subjected to thermogravimetric analysis. Figure 2 As shown in the figure, it can be seen that the mass loss of HGMs@SA-1.5 from room temperature (30℃) to 200℃ is 6.99%, and the mass loss of HGMs is 3.92%. Generally, the mass loss of materials below 200℃ is related to the volatilization of water, so the moisture content of HGMs@SA-1.5 and HGMs is 6.99% and 3.92%, respectively. In the temperature range of 200℃ to 700℃, the mass loss of HGMs@SA-1.5 is 16.01%. It has been reported in the literature that the mass loss above 200℃ may be related to the degradation of organic matter. Therefore, it can be inferred that the organic matter content on HGMs@SA is 16.01%. At the same time, the mass loss of HGMs@SA-1.5 at 30-50℃ is 1.28%, and the mass loss at 100℃ is 4.07%, and the mass loss is relatively small.

[0037] The strain curves (mechanical properties) of SA-1.5 and HGMs@SA-1.5 are shown in Figure 2. Figure 3 As shown in the figure, it can be seen that the strain value of SA-1.5 reaches 21.87%, and the corresponding stress is 2.38kPa. During the HGMs loading process, the strain value of HGMs@SA-1.5 reaches 27.74%, and the corresponding stress is 8.52kPa. In addition, during the entire strain process, the stress value of HGMs@SA-1.5 is always higher than that of SA-1.5. Therefore, adding HGMs to SA greatly improves its strength and tensile properties.

[0038] 2. Cadmium adsorption experiment:

[0039] Add 20 mL of 100 mg / L Cd 2+20 mg of SA-1, SA-1.5, SA-2, and SA-2.5 were added to the solution for adsorption experiments. The adsorption experiments were carried out in a constant temperature oscillator with the temperature set at 25°C and the speed set at 220 rpm. After constant temperature oscillation for 24 hours, samples were taken and the cadmium content in the solution was determined by flame atomic absorption spectrophotometry. The results are as follows: Figure 4 As shown in the figure, it can be seen that with the increase of the mass fraction of sodium alginate solution, the adsorption amount decreases.

[0040] Example 2

[0041] Weigh 10 portions of 20 mg HGMs@SA-1.5 prepared in Example 1 and add them into 20 mL of 10, 20, 30, 40, 50, 60, 80, 100, 150, and 300 mg·L -1 CD 2+ The solution pH was 0.1 mol·L -1 HCl and NaOH were used to adjust the initial pH value to 6±0.2. The adsorption test was carried out in a constant temperature oscillator with the temperature set at 25°C and the rotation speed at 220 rpm. The samples were taken after constant temperature oscillation for 24 hours. 2+ The concentration was measured by flame atomic absorption spectrophotometry and the Cd 2+ The adsorption amount.

[0042] At 25℃, HGMs@SA-1.5 has a significant effect on Cd 2+ The isotherm adsorption curve is as follows Figure 5 As shown in the figure, within 24 hours, HGMs@SA-1.5 2+ The adsorption capacity of Cd 2+ The initial concentration increases with the increase of Cd 2+ The initial concentration of the solution is higher than 100 mg·L -1 When the adsorption capacity increases, the rate of increase slows down and gradually reaches the maximum saturated adsorption capacity, and the maximum adsorption capacity reaches 55.84 mg·g -1 As the initial concentration of the solution increases, the slope of the adsorption curve decreases and the rate of increase of the adsorption amount slows down. 2+ Initial concentration greater than 100 mg·L -1 When the initial Cd 2+ When the concentration is low, the functional groups and adsorption sites on the adsorbent surface are not fully occupied. 2+ As the concentration increases, more adsorption sites on the adsorbent surface are gradually occupied, and the adsorbent is more sensitive to Cd 2+ The adsorption amount of Cd 2+When the concentration of Cd reaches a certain value, the adsorption sites on the adsorbent surface are completely occupied, and the adsorption capacity of the adsorbent reaches saturation, resulting in the adsorption of Cd by HGMs@SA-1.5. 2+ The adsorption amount reaches the maximum value. The adsorption data are fitted using the Langmuir and Freundich models, and the fitting results are as follows:

[0043]

[0044] As can be seen from the above table, the Langmuir adsorption model and the Freundlich adsorption model can fit HGMs@SA-1.5 well, R 2 The Langmuir adsorption model has a better fitting effect on HGMs@SA-1.5, indicating that the active sites on the surface of the adsorbent are evenly distributed and the adsorption of Cd 2+ The adsorption is a monolayer adsorption driven by chemical adsorption. According to the Langmuir adsorption model equation, the maximum adsorption capacity of HGMs@SA-1.5 is calculated to be 55.84 mg·g -1 The model constant b in the Langmuir fitting parameters is between 0 and 1, indicating that it can be well applied to Cd 2+ The adsorption of the solution, and in the Freundlich fitting parameters, n>1 indicates that the adsorption process is favorable.

[0045] Example 3

[0046] Weigh the HGMs@SA-1.5 prepared in Example 1 and add it to a flask with an initial concentration of 100 mg·L -1 CD 2+ In the solution, the amount of HGMs@SA-1.5 added was 1 g / L, and the solution pH was 0.1 mol·L -1 HCl and NaOH were used to adjust the initial pH value to (6 ± 0.2). The adsorption test was carried out in a thermostatic oscillator with the temperature set at 25 °C and the rotation speed at 220 rpm. The samples were taken at 0, 1, 2, 3, 5, 10, 20, 30, 45, 60, 120, 240, 360, 720, 1440, 2880, 4320, 5760 and 7200 min to separate the solid particles and the Cd in the solution. 2+ The concentration was measured by flame atomic absorption spectrophotometry and the Cd 2+ The adsorption amount.

[0047] At a temperature of 25°C, Cd 2+ The solution concentration is 100 mg·L -1 , HGMs@SA-1.5 was subjected to Cd2+ The adsorption kinetics test results are as follows Figure 6 As shown in the figure, the adsorption amount of Cd2+ in the solution by HGMs@SA-1.5 increases with the increase of adsorption time, and the adsorption speed shows a trend from fast to slow. The adsorbent and the solution can reach the adsorption equilibrium state within 72 hours. Within the first 24 hours of adsorption, the adsorbent can reach 72.23% of the maximum adsorption amount. This is because in the initial stage of adsorption, Cd2+ in the solution 2+ The concentration is relatively high, and there are a large number of HGMs@SA-1.5 surfaces that can react with Cd 2+ active site where binding occurs, thus 2+ The adsorption rate is fast. As the adsorption process proceeds, more and more Cd 2+ It is adsorbed onto the adsorption active sites on the surface of HGMs@SA-1.5. In the middle and late stages of adsorption, the adsorption active sites on the surface of HGMs@SA-1.5 are gradually occupied, and the adsorption active sites become fewer. At the same time, Cd 2+ As the concentration decreases, the adsorption rate of HGMs@SA-1.5 gradually decreases until it reaches adsorption equilibrium.

[0048] In order to further explore the effect of HGMs@SA-1.5 on Cd 2+ The adsorption process was carried out by fitting the adsorption data using pseudo-first-order kinetics and pseudo-second-order kinetics adsorption models. The fitting parameter results are shown in the following table:

[0049]

[0050] From the above table, we can see that the fitting effect of the pseudo-second-order kinetic model is better than that of the pseudo-first-order kinetic model. At the same time, the adsorption capacity of the adsorbent material at adsorption equilibrium is calculated by the pseudo-second-order kinetic model to be 42.21 mg g -1 , with a maximum adsorption capacity of 55.84 mg·g -1 The results of the model fitting parameters show that HGMs@SA-1.5 has a good adsorption performance on Cd 2+ The adsorption process of Cd is mainly dominated by chemical adsorption. There are a large number of polar functional groups such as -OH and -COO on its surface. The adsorption rate is related to the interaction between these polar functional groups and Cd 2+ The chemical bonds between the HGMs@SA-1.5 surface polar functional groups such as -OH and -COO interact with Cd 2+ Electrostatic adsorption occurs, and then Cd is captured by coordination 2+ .

[0051] Example 4

[0052] Weigh 11 portions of 10 mg of HGMs@SA-1.5 prepared in Example 1 and add them to 10 mL of a 100 mg / L -1 CD 2+ The solution pH was adjusted by HCl and NaOH, and the initial pH value was adjusted to 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 and 12. The temperature was set at 25 °C and the speed was 220 rpm. After constant temperature shaking for 24 h, the sample was taken and the supernatant was filtered and then the Cd content in the solution was measured by flame atomic absorption spectrophotometry. 2+ concentration, calculate the adsorption of Cd by adsorption materials at different pH 2+ The adsorption amount was measured and the pH of the equilibrium solution was measured.

[0053] The results are as follows Figure 7 As shown in the figure, it can be clearly seen that the adsorbent HGMs@SA-1.5 has a strong effect on the adsorption of Cd 2+ The adsorption of Cd depends largely on the pH value. Specifically, when the pH is 2, the adsorption amount is extremely low, only 5.13 mg / g. When the initial pH value of the solution increases from 2 to 6, the adsorption capacity increases significantly, from 5.13 mg / g to 38.2 mg / g. This phenomenon shows that the pH value of the solution has a great influence on the adsorption of Cd. 2+ It has a great influence on the adsorption on HGMs@SA-1.5.

[0054] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing an adsorbent material, characterized in that: The specific steps include: (1) Treat the hollow glass microspheres with an alkaline solution and set aside; (2) adding sodium alginate into pure water and stirring to obtain a sodium alginate solution with a mass fraction of 1 to 2.5%; (3) adding the hollow glass microspheres treated in step (1) into the sodium alginate solution and stirring evenly to obtain a hollow glass microsphere-sodium alginate solution; then aspirating the hollow glass microsphere-sodium alginate solution with a syringe and adding dropwise into a 0.1-0.5 mol / L calcium chloride solution; after standing for 12-24 hours, filtering, washing, and freeze-drying, the adsorption material is obtained.

2. The method for preparing an adsorption material according to claim 1, characterized in that: The alkaline solution is a sodium hydroxide solution.

3. The method for preparing an adsorption material according to claim 1 or 2, characterized in that: The specific steps of alkali treatment of hollow glass microspheres are: adding the hollow glass microspheres to an alkali solution, then heating in a water bath at 70-90°C, stirring at a speed of 150-200 r / min for 90-120 min, standing and cooling, filtering the alkali solution, washing with anhydrous ethanol and pure water three times each, and drying.

4. The method for preparing an adsorption material according to claim 1, characterized in that: The mass ratio of sodium alginate to hollow glass microspheres is 1:3~4.

5. An adsorption material, characterized in that: The adsorbent is prepared by the method for preparing an adsorbent material as shown in any one of claims 1 to 4.

6. The method for removing heavy metal cadmium from paddy soil by using an adsorption material according to claim 5, characterized in that: The specific steps include: S1. Activation: Add 0.02-0.05 mol / L ferric chloride aqueous solution to paddy soil, stir and activate for 24-36 hours, so that the fixed cadmium in the paddy soil is converted into cadmium ions; S2. Adsorption: Add the adsorption material described above and stir for at least 72 hours; S3. Flotation: Recover the adsorbent material floating on the water surface, desorb and wash the adsorbent material to achieve the recycling of the adsorbent material.

7. The method for removing heavy metal cadmium from paddy soil by using an adsorption material according to claim 6, characterized in that: The mass ratio of paddy soil and ferric chloride aqueous solution is 1:1.5~2.

5.

8. The method for removing heavy metal cadmium from paddy soil by using an adsorption material according to claim 6, characterized in that: The amount of adsorption material added is: the mass of adsorption material added is 0.5%-1% of the mass of paddy soil.

Citation Information

Cited By

  • Adsorbent for remediation of heavy metal contaminated soil, preparation method and application

    CN120393937B